Europe Sees Mixed Results From Public-Private Partnerships For Building And Managing Health Care Facilities And Services - Barlow,JG; Roehrich,J; Wright,S (Health Affairs, 2013)
Prompted in part by constrained national budgets, European governments are increasingly partnering with the private sector to underwrite the costs of constructing and operating public hospitals and other health care facilities and delivering services. Through such public-private partnerships, governments hope to avoid up-front capitalexpenditure and to harness private-sector efficiencies, while private-sector partners aim for a return on investment. Our research indicates that to date, experience with these partnerships has been mixed. Early models ofthese partnerships—for example, in which a private firm builds a hospital and carries out building maintenance, which we term an“accommodation-only” model—arguably have not met expectations for achieving greater efficiencies at lower costs. Newer models described in this article offer greater opportunities for efficiency gains but areadministratively harder to set up and manage. Given the shortages in public capital for new infrastructure, it seems likely that theattractiveness of these partnerships to European governments will grow.